Effects of Project-Based Learning, STEM Education, and Culture-Based Learning on K-12 Mathematics Achievement: A Meta-Analysis - Ranak Lince; Husnaeni Husnaeni (Sakura Digital Nusantara, 2026)
Purpose: This study evaluates and compares the effectiveness of Project-Based Learning (PjBL), STEM/STEAM, and Culture-Based Learning (CBL) on students’ mathematics achievement to address fragmented findings in existing literature. Methods: A systematic review and meta-analysis following PRISMA guidelines was conducted on 34 empirical studies published between 2015 and 2025 across four major academic databases: Scopus, ERIC, ScienceDirect, and Sinta. Effect sizes were calculated using Cohen’s d and analyzed with a random-effects model. Findings: All three student-centered approaches significantly improve mathematics achievement, with a large pooled effect size (d = 0.99). Subgroup analysis revealed that CBL yielded the highest effect size (d = 1.50), followed by STEM/STEAM (d = 1.07), and PjBL (d = 0.74). High heterogeneity indicates effectiveness is heavily influenced by contextual implementation factors. Research Implications: The findings recommend that educators and curriculum developers integrate contextual, project-based, and interdisciplinary approaches to enrich mathematics learning and bridge abstract concepts with students' real-world experiences. Originality: This research provides a unique contribution by systematically comparing the relative strengths of PjBL, STEM/STEAM, and CBL within a single analytical framework, demonstrating the strong potential for an integrated hybrid pedagogical model in mathematics education.